Modelling Modal Shift Preference of Freight Transport on Surabaya-Jakarta Corridor : A Preliminary Survey - R, Hartono Guntur; Mochtar, Indrasurya B; Widyastuti, Hera (Institut Teknologi Sepuluh Nopember, 2017)
The market share of freight transport which is dominated by road transport and accompanied by unbalanced of infrastructure’s growth and freight demand has created various negative impacts on existing transportation system. The shift of freight transport from road to rail and sea is expected to reduce those impacts. Research on the behavior of freight mode choice and the extent to which the user is willing to trade off the attribute change needs to be done so that the amount of modal shift will be known. The main objective of the study was to produce a model of mode choice based on preference surveys among forwarders, as well as to provide inputs for policy improvement and or improvement of freight transportation services. One of the surveys to be conducted is the revealed preference (RP) survey. The important stage before the RP survey is to conduct a preliminary survey. This stage aims to determine the important trends related to the choice of modes by the forwarder and test the response rate of respondents. The survey is also useful for assessing the credibility of the data instrument, identifying potential errors in the data instrument, and determining non-conformities in survey management before the actual survey. Data collection was done by sending questionnaires. The structure of the questionnaire consists of questions about characteristics of : shipment, travel, and modes. The results of survey showed relatively low response rate because it was only 8 respondents who were willing to answer the questionnaire. This indicates that the questionnaire needs to be combined with other methods, such as: face to face interviews and or focus groups. The results of the preliminary survey show that the main factors for the choice of existing modes are: shipment costs, loss/damage, and time travel. The implementation of the next stage survey should consider that each company has more than one shipping commodity so it is necessary to group questions and analysis based on each commodity.